Chromatin accessibility reveals potential prognostic value of the peak set associated with smoking history in patients with lung adenocarcinoma - Han Liang; Jianlian Deng; Tian Luo; Huijuan Luo; Fuqiang Li; Kui Wu; Cong Lin (Heliyon)
Considerable differences in molecular characteristics have been defined between non-smoker and smokers in patients with lung adenocarcinoma (LUAD), yet studies on open chromatin patterns associated with LUAD progression caused by smoking are still lacking. Here, we constructed a novel network based on correlations between each ATAC-seq peak from TCGA data using our previously developed algorithm. Subsequently, principal component analysis was performed on LUAD samples with retained peaks filtered by the correlation network, and pathway analysis was conducted to identify potential pathways involved. We identified a set of peaks that discriminated smokers in LUAD patients according to levels of exposure to tobacco quantified in pack-years. These peaks were also significantly associated with progression-free survival and overall survival of these patients. Further examination of the gene set related to those peaks revealed that the comprising genes, such as KRT19, B3GNT3, CLDN7 and CLDN3 are strongly associated with LUAD development. They are consistent with the important roles of the associated pathways in LUAD oncogenesis induced by smoking, including estrogen response, apical junction and glycolysis pathways. In summary, our study may provide valuable insights into exploring ATAC-seq peaks and understanding smoking-related LUAD carcinogenesis from a perspective of open chromatin changes.